Community Violence Exposure and Stress Reactivity in African American and Non-Latino White Adolescents With Overweight/Obesity - Hasson, Rebecca E. (Journal of interpersonal violence, 2022)
Adolescents who experience community violence are exposed to toxic stressors at a critical period of growth and development. The purpose of this study was to examine the relationship between community violence exposure and stress reactivity in African American and non-Latino white adolescents with overweight/obesity. Fifty-one adolescents (47% female, 55% African American; aged 14?19) participated in this study. Community violence was assessed using the Survey of Children?s Exposure to Community Violence. Stress reactivity was assessed via salivary cortisol and alpha-amylase area under the curve (AUC) during a Trier Social Stress Test (TSST). Race was a significant predictor of alpha-amylase reactivity (? = 10740±3665, p = 0.0006), with a higher alpha-amylase AUC observed in African American compared to non-Latino white adolescents. There was also a significant difference in the relationship between community violence exposure and alpha-amylase AUC by race (? = ?3561±1226, p = 0.007). At similar increases in violence exposure, African Americans demonstrated a significant decline in alpha-amylase AUC while non-Latino whites demonstrated a significant increase in alpha-amylase AUC. Neither race nor violence exposure were significant predictors of cortisol AUC and there were no significant differences in the relationship between community violence exposure and cortisol AUC by race (all p?s > .05). These preliminary findings suggest exposure to community violence may act to exacerbate autonomic dysregulation in African American adolescents with overweight/obesity. Longitudinal studies are needed to confirm the mechanisms by which community violence exposure differentially impacts stress responses by race.